Bahasa Mantra Sasak Tinjuan Makna Asosiatif - Idham, Idham (STKIP PGRI Jombang, 2019)
This study describes and explains in detail the linguistic meaning of the Sasak mantra, the function of the mantra, and the text structure of the Sasak mantra. The meaning of the mantra is also related to the culture that exists in the area that is the location of the research. The method used in this study is a descriptive qualitative method and ethnographic method. wind, jelo, full moon, sea, gumi, sky, and betu are used to produce a strong suggestion. (2) plant symbols, namely angn, apuh, buaq, mako, glemper, shoots, tojang, paoq kayuk, and flower are used to cause the suggestion of attractiveness. (3) animal symbols, namely yellow kecial, jaran guying, kolo, ptuk and propeller. The term 'kecial kuning' is used to give rise to suggestion of attractiveness, the term jaran guyang has the effect of suggesting strength. The term kolo, ptuk, balang has the effect of suggesting damage. (4) mythical symbols, namely the terms bidederi-bidedere, mas bejeboh, mentinggang mentang, crazy singang, betara guru, betara lenjang, and goldfish. Bidederi-bidedere is used to cause the effects of beauty suggestion. Mas Bejeboh authority. Singgang mentune, singang crazy, betara guru is used to cause suggestions of the authorities of the springs. Betara levels are used to cause the suggestion of the ruler of the rain. (5) Islamic religious symbols, namely basmlah, creed, kun fayakun, Prophet Muhammad, alif, Allah, prophet David, prophet Sulaiman, Syaidina Ali, Assalamu, Prophet Allah Adam, Jibrail, Fatimah-Fatimah. The existence of a term in Islamic religious signifies the language of the mantra that the people of Lombok are very religious and believe that chosen beings such as prophets, guardians, angels, prophet's friends can be used as mediators in asking for something.